Risk factors of hypocalcemia after total thyroidectomy. A high volume center experience - İnanç, Ömer Faruk; Çetin, Kenan; Tosun, Yasin; Küçük, Hasan Fehmi (Frontiers in Endocrinology, 2025)
IntroductionThyroidectomy is one of the most frequently performed surgical procedures worldwide. The most common complication of total thyroidectomy (TT) in the early postoperative period is hypocalcemia. This study aims to determine the risk factors for postoperative hypocalcemia after TT and to reveal their clinical value. As a secondary outcome, we assessed the effects of iatrogenic parathyroidectomy, surgical experience, and parathyroid transplantations on prolonged than one month hypocalcemia and intravenous calcium infusion requirement after TT.MethodsWe designed our study as a retrospective cohort study. Two hundred sixty-three patients that underwent total thyroidectomy in a single tertiary endocrine surgery unit were included. Patients are followed up for 6 months. The study performed between April 2014 and March 2015. Patients were divided into two groups according to the presence or absence of hypocalcemia after surgery. All patients who performed total thyroidectomy without lymph node dissection in a single session were initially included in the study cohorts. Thereafter, patients with preoperatively confirmed hyperparathyroidism, hypoparathyroidism/hypocalcemia, had a history of thyroid operation, and postoperatively did not undergo regular follow-up (min. 12 months after surgery) were excluded from the latter analysis.ResultsIn the multivariate analysis we conducted in our study, we found that female gender, preoperative hyperthyroidism, intraoperative parathyroid autotransplantation, and surgical experience were independent risk factors. Some of them are predictable parameters such as surgeon experience and preoperative hyperthyroidism.ConclusionsWe consider that specific theoretical and practical studies on thyroid surgery will reduce postoperative hypocalcemia.